Juvenile Neuropsychiatric Systemic Lupus Erythematosus With Magnetic Resonance Imaging Findings Similar to Acute Necrotizing Encephalopathy. (December 2021) - Korenaga, Yuno; Wakiguchi, Hiroyuki; Matsushige, Takeshi; Inoue, Hirofumi; Mizutani, Makoto; Furuta, Takashi; Kawamura, Mai; Nakamura, Tamaki; Okazaki, Fumiko; Yasudo, Hiroki; Maki, Takashi; Hasegawa, Shunji
Abstract : Supplemental digital content is available in the text.